Incidence of Staphylococcus aureus in cows' milk following mucosal and parenteral administration of autogenous S. aureus vaccine during the dry period - melach@vodamail.co.za (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria,2012.